2020
DOI: 10.1186/s12913-020-05137-1
|View full text |Cite
|
Sign up to set email alerts
|

What explains the regional variation in the use of general practitioners in Australia?

Abstract: Background: Regional variation in the use of health care services is widespread. Identifying and understanding the sources of variation and how much variation is unexplained can inform policy interventions to improve the efficiency and equity of health care delivery. Methods: We examined the regional variation in the use of general practitioners (GPs) using data from the Social Health Atlas of Australia by Statistical Local Area (SLAs). 756 SLAs were included in the analysis. The outcome variable of GP visits … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 20 publications
(38 reference statements)
0
15
0
Order By: Relevance
“…Findings highlight the many lower socio-economic regions in Australia with a lack of affordable services. Several authors have reported differences in Australian GP distribution, utilisation and GP employment locality choices within lower SES area levels (Roeger et al 2010;McRae and Butler 2014;Lyle and Hendrie 2019;McIsaac et al 2019;Mu and Hall 2020). In contrast, a study published two decades ago documented high GP hours per population and higher bulk billing rates in the most disadvantaged areas in compari-Fig.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Findings highlight the many lower socio-economic regions in Australia with a lack of affordable services. Several authors have reported differences in Australian GP distribution, utilisation and GP employment locality choices within lower SES area levels (Roeger et al 2010;McRae and Butler 2014;Lyle and Hendrie 2019;McIsaac et al 2019;Mu and Hall 2020). In contrast, a study published two decades ago documented high GP hours per population and higher bulk billing rates in the most disadvantaged areas in compari-Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Business sustainability and market forces greatly impact the viability of bulk billing-only practices and billing models (Royal Australian College of General Practitioners 2018). There are few studies examining bulk billing practices and of these few, bulk billing behaviour is suggested to be influenced by regional area status, practice size, consultation length, patient income and practice location (Britt et al 2004;Achat et al 2010;De Abreu Lourenco et al 2015;Mu and Hall 2020;O'Sullivan et al 2022).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations